(untitled) (Revista de Estudos em Municipalidade, 2026)
This article, the result of a bibliographical review based on criticism from the Sociology of Work, reflects on how changes in the world of work, especially technological have had a degrading impact on the working conditions and relationships of the working class as a whole. The text brings some theoretical elements of the relationship between work and new technologies, with emphasis on the concept of platformization, situating the contradictions that permeate this relationship, inscribed in the dynamics of capitalist sociability.